2016
DOI: 10.1139/cjm-2016-0129
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of 1377C/T polymorphism of the Toll-like receptor 3 among patients with chronic hepatitis B

Abstract: The immunopathogenesis of chronic hepatitis B (CHB) has not been clarified yet. Toll-like receptors (TLR) are a receptor family that initiates immunity with exogenous-endogenous ligands and plays a role in the pathogenesis of infections. In this study, we aimed to investigate the frequency of TLR 3 1377C/T (rs3775290) polymorphism and its role in patients with CHB. We included 50 healthy individuals as control group and 73 active and 43 inactive hepatitis B patients. All DNA samples were isolated from blood sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
4
1
2
Order By: Relevance
“…This finding partially agreed with the findings of another Egyptian study that showed a significantly higher ‘T' allele of TLR3 rs3775290 in hepatitis C virus (HCV) patients than healthy controls; however, the heterozygous genotype ‘C/T' was higher than both homozygous genotypes in HCV patients than controls [ 24 ]. On the other hand, our finding was in contrary with the Turkish study of Goktas et al [ 25 ], which revealed that ‘C/C' genotype was a risk factor for chronic HBV infection. These controversial findings could be due to the variations in ethnic background of the studied populations, the studied infectious diseases and the number of patients and controls.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding partially agreed with the findings of another Egyptian study that showed a significantly higher ‘T' allele of TLR3 rs3775290 in hepatitis C virus (HCV) patients than healthy controls; however, the heterozygous genotype ‘C/T' was higher than both homozygous genotypes in HCV patients than controls [ 24 ]. On the other hand, our finding was in contrary with the Turkish study of Goktas et al [ 25 ], which revealed that ‘C/C' genotype was a risk factor for chronic HBV infection. These controversial findings could be due to the variations in ethnic background of the studied populations, the studied infectious diseases and the number of patients and controls.…”
Section: Discussioncontrasting
confidence: 99%
“…The role of SNP rs3775290 in viral aetiology has received much attention in the last few years (52). For example, interferon-stimulated response elements were found whilst studying the promoter sequence of TLR3 in silico (30).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Goktas et al . 26 reported that in Turkish patients with active CHB there was a higher prevalence of the CC genotype of the TLR3 SNP rs3775290, which is located close to rs3775291. They suggest that the wild-type might lead to a stronger immune response against HBV.…”
Section: Discussionmentioning
confidence: 99%